Interference of daratumumab and efficacy of plerixafor on haematopoietic stem cell collection in Multiple Myeloma - Bigi, Flavia; Tacchetti, Paola; Giorgi, Alessandro; Mazzocchetti, Gaia; Solli, Vincenza; Barbato, Simona; Sinigaglia, Barbara; Campanini, Elena; Favero, Emanuele; Talarico, Marco; Puppi, Michele; Rizzello, Ilaria; et al. (Frontiers in Hematology, 2024)
The impact of daratumumab on CD34+ hematopoietic stem cell (HSC) mobilization has recently been a matter of concern. To address this issue, we compared CD34+ HSC-related outcomes in patients with multiple myeloma treated with daratumumab-based quadruplets (N = 44) and bortezomib/thalidomide/dexamethasone (N = 50) before cyclophosphamide-based mobilization. Plerixafor was more often required in the daratumumab group (52% vs. 20%, p = 0.002) and, despite a lower total yield, retained its efficacy in boosting HSC harvesting (+90% vs. +79%, p = 0.463). As a result, the same proportion of patients reached their planned collection goal in the two groups, suggesting its potential to overcome the interference of daratumumab on HSC mobilization. No clinically significant differences were observed in the immediate post-autologous HSC transplant interval in the two groups.